Meaningful engagement: A crossfunctional framework for digital therapeutics - Strauss, Gabriel; Flannery, Jessica E.; Vierra, Elise; Koepsell, Xin; Berglund, Emily; Miller, Ian; Lake, Jessica I. (Frontiers in Digital Health, 2022)
Digital mental health interventions, or digital therapeutics, have the potential to transform the field of mental health. They provide the opportunity for increased accessibility, reduced stigma, and daily integration with patient’s lives. However, as the burgeoning field continues to expand, there is a growing concern regarding the level and type of engagement users have with these technologies. Unlike many traditional technology products that have optimized their user experience to maximize the amount of time users spend within the product, such engagement within a digital therapeutic is not sufficient if users are not experiencing an improvement in clinical outcomes. In fact, a primary challenge within digital therapeutics is user engagement. Digital therapeutics are only effective if users sufficiently engage with them and we argue, only if users meaningfully engage with the product. Therefore, we propose a 4-step framework to assess meaningful engagement within digital therapeutics: 1) Define the measure of value 2) Operationalize meaningful engagement for your digital therapeutic 3) Implement solutions to increase meaningful engagement 4) Iteratively evaluate the solution’s impact on meaningful engagement and clinical outcomes. We provide recommendations to the common challenges associated with each step. We specifically emphasize a cross-functional approach to assessing meaningful engagement and use an adolescent-focused example throughout to further highlight developmental considerations one should consider depending on their target users.